2008
DOI: 10.1080/17453670810016731
|View full text |Cite
|
Sign up to set email alerts
|

Surgical inaccuracy of tumor resection and reconstruction within the pelvis: An experimental study

Abstract: Background and purpose Osseous pelvic tumors can be resected and reconstructed using massive bone allografts. Geometric accuracy of the conventional surgical procedure has not yet been documented. The aim of this experimental study was mainly to assess accuracy of tumoral resection with a 10-mm surgical margin, and also to evaluate the geometry of the host-graft reconstruction.Methods An experimental model on plastic pelvises was designed to simulate tumor resection and reconstruction. 4 experienced surgeons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 29 publications
0
76
1
3
Order By: Relevance
“…Additionally, the angles of inclination between the target plane and best-fit planes were calculated. Similar to previous reports [6,7] and to ISO parameters [12], the angles of inclination were measured by projecting the target and resection planes in a plane parallel to the approximate anatomic AP axis of the femur (the front angle) and in a plane approximately parallel to the anatomic sagittal axis of the femur (the depth angle) (Fig. 10).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the angles of inclination between the target plane and best-fit planes were calculated. Similar to previous reports [6,7] and to ISO parameters [12], the angles of inclination were measured by projecting the target and resection planes in a plane parallel to the approximate anatomic AP axis of the femur (the front angle) and in a plane approximately parallel to the anatomic sagittal axis of the femur (the depth angle) (Fig. 10).…”
Section: Methodsmentioning
confidence: 97%
“…In reality, however, the standard tools and techniques used by orthopaedic surgeons can substantially limit the ability to reliably and consistently reproduce the ideal preoperative plan at the time of resection [6] with potentially serious consequences. For instance, the surgeon may inadvertently cut into the tumor during surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Intraoperatively, image guidance with the help of fusion images provided precise visual orientation. Cartiaux et al [7] investigated the surgical accuracy of an experienced surgeon in performing a pelvic tumor resection with a 1-cm surgical margin. They reported that the surgeon could achieve a 1-cm surgical margin (± 5 mm) with a probability of only 52%.…”
Section: Discussionmentioning
confidence: 99%
“…Cartiaux et al demonstrated that even in an ideal surgical situation, with four experienced surgeons operating on plastic pelvic models with complete visualization and accessibility to bone surfaces, the probability of achieving a good surgical margin was only 52% (95% CI: 37-67%). In addition, reconstruction correlations between host-graft junction parameters were found to be poor [4]. A subsequent geometrical model study by Cartiaux et al demonstrated that improvements in cutting accuracy could be achieved when CAOS was integrated into a freehand bone-cutting process [5].…”
Section: Introductionmentioning
confidence: 99%